2016
DOI: 10.1016/j.cej.2015.11.072
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of single and two stage, mesophilic and thermophilic high rate systems for anaerobic digestion of corn stalk

Abstract: General rightsCopyright for the publications made accessible via the Edinburgh Research Explorer is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. Take down policyThe University of Edinburgh has made every reasonable effort to ensure that Edinburgh Research Explorer content complies with UK legislation. If you believe that the public display of this file breach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…In addition, there were no statistical differences in the k H at I/S of 2:1 and 1:1, remaining around 0.10–0.15 1/d, which concurs with typical values obtained in energy crops (Meng et al, 2016 ). The I/S of 1:2 considerably decreased the k H values, which may be due to biomass transfer problems due to bad mixing or inhibition by organic acids accumulation, as has been claimed previously in BMP standardization procedures (Holliger et al, 2016 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, there were no statistical differences in the k H at I/S of 2:1 and 1:1, remaining around 0.10–0.15 1/d, which concurs with typical values obtained in energy crops (Meng et al, 2016 ). The I/S of 1:2 considerably decreased the k H values, which may be due to biomass transfer problems due to bad mixing or inhibition by organic acids accumulation, as has been claimed previously in BMP standardization procedures (Holliger et al, 2016 ).…”
Section: Resultssupporting
confidence: 90%
“…The kinetic analysis confirmed that the IL treatment only increased slightly the methane potential in thermophilic conditions (Figure 6A ). A B 0 value of 379 ± 16 LCH 4 /kgTS for a I/S of 2:1 was obtained after IL pre-treatment, which is higher than other values obtained for energy crops at thermophilic conditions (Meng et al, 2016 ).…”
Section: Resultscontrasting
confidence: 54%
“…This resulted in faster methane production by 40% compared to the system without recirculation. Application of an anaerobic filter on digestion of corn stalk using an upflow anaerobic solid‐state (UASS) at different organic loading rates increased the methane yield from 39–184 to 84–201 mL g −1 VS under mesophilic conditions . Zuo et al also reported that the effect of recirculation in two‐stage AD of vegetable waste is more pronounce when the system runs at a high OLR (above 2.6 g VS L −1 day −1 ).…”
Section: High‐rate Second‐stage Processmentioning
confidence: 99%
“…Large amounts of harvest corn straw is becoming dry and discarded in the field, which results in a large loss of carbohydrates and soluble components during the drying process. DCS is generally associated with lower biogas production [14] . Therefore, it is of great significance to study an efficient, stable and safe method to convert corn straw into renewable energy.…”
Section: Introductionmentioning
confidence: 99%